Playfulness as a Relevant Lexeme in the Bilingual Linguistic Consciousness of Ukrainian People - Sypko, Artem; Hordiyenko-Mytrofanova, Iya (East European Journal of Psycholinguistics, 2015)
The article describes the results of the free association experiment with the stimulus word “playfulness”. The total number of respondents amounted to 3,300 people. The analysis of the associations convincingly proved that in terms of its functioning “playfulness” is a relevant lexeme in the bilingual linguistic consciousness of Ukrainian people. The further step of the research was aimed at revealing common and specific features of respondents representing different “profession types”: “person-nature”, “person-person”, “person-sign systems”, “person-technology”, “person-artistic image”. The sample involved 500 people, with 100 people for each “profession type”, men and women being equally represented. The overall number of reactions amounted to 2,452 (including word combinations and sentences (88)), with 270 occurring more than once, and 503 singular reactions. The analysis of the most frequent reactions revealed certain common features in the verbal behavior of the respondents, reflected in the lexemes “merry-making” (96(3.915)), “delight” (80(3.262)), “flirting” (79(3.221)), “laughter” (70(2.855)), “champagne” (49(1.998)), “a young girl” (46(1.876)), “children” (43(1.754)), “mood” (42(1.713)), “coquetry” (37(1.509)), “happiness” (31(1.264)), “smile” (30 (1.223%)). The analysis of singular reactions revealed the impact of professional activity on the understanding of playfulness. The procedures of sememic attribution and semic interpretation made it possible to outline the meanings of the lexeme “playfulness” and formulate their definitions as a coherent enumeration of the identified semantic components. References Gordienko-Mitrofanova, I. V. (2014). Psikhologicheskaya interpretatsiya leksikograficheskogo opisaniya slova «igrivyy» [Psychological interpretation of lexicographic description of the word «playfulness»]. Problemy Suchasnoyi Psikhologії, 25, 83–98. Gordienko-Mitrofanova, I. V. (2014). Leksikograficheskoe znachenie slova «igrivost’» (podgotovitel’nyy etap psikholingvisticheskogo eksperimenta) [Lexicographic meaning of the word «playfulness» (preparatory stage of the psycholinguistic experiment)]. Psyhologichni Perspektyvy Psikholohіyi, 24, 76–88. Csikszentmihalyi, M. (1975). Play and intrinsic rewards. Journal of Humanistic Psychology, 15, 41–63. Bowman, J.R. (1987). Making work play. In: Meaningful Play, Playful Meanings (pp. 61– 71). G.A. Fine (ed.). Champaign, IL: Human Kinetics. Glynn, M.A., & Webster, J. (1993). Refining the nomological net of the Adult Playfulness Scale: personality, motivational and attitudinal correlates for highly intelligent adults. Psychological Reports, 72, 1023–1026. Amabile, T.M., Hill, K.G., Hennessey, B.A., Tighe, E.M. (1994). The Work Preference Inventory: Assessing intrinsic and extrinsic motivational orientations. Journal of Personality and Social Psychology, 66(5), 950–967. Tsuji, Hit., Tsuji, Hei., Yamada, S., Natsuno, Y., Morita, Y., Mukoyama, Y., Hata, K., Fujishima, Y. (1996). Standardization of the Five Factor Personality Questionnaire: Factor structure. International Journal of Psychology, 31, 103–217. Bozionelos, N., & Bozionelos, G. (1997). Psychology of computer use: XLVIII: Relation between playfulness and computer anxiety. Psychological Reports, 81, 956–958. Dunn, L. L. S. (2004) Cognitive playfulness, innovativeness, and belief of essentialness: Characteristics of educators who have the ability to make enduring changes in the integration of technology into the classroom environment. Ph.D. dissertation. Retrieved from: http://digital.library.unt.edu/ark%3A/67531/metadc4620/ Yu, P., Wu, J-J., Chen, I., Lin, Y.T. (2007). Is playfulness a benefit to work? Empirical evidence of professionals in Taiwan. International Journal of Technology Measurement, 39(3/4), 412–429. Tan, J. P-L. (2009) Digital kids, analogue students: A mixed methods study of students’ engagement with a school-based Web 2.0 learning innovation. (Unpublished doctoral dissertation.) Centre for Learning Innovation, Faculty of Education Queensland University of Technology, Australia. Proyer, R.T. (2011). Being playful and smart? The relations of adult playfulness with psychometric and self-estimated intelligence and academic performance. Learning and Individual Differences, 21, 463–467. Proyer, R.T., Ruch W. (2011). The virtuousness of adult playfulness: the relation of playfulness with strengths of character, Psychology of Well-Being: Theory, Research and Practice, 1, 4. Tan J., McWilliam E.(2013) Cognitive playfulness, creative capacity and generation. Lifelong education: the XXI century, 2, 1–9. doi: 10.15393/j5.art.2013.2090. Huizinga, J. (2003). Homo Ludens, Moscow: Ayris-press. Gordienko-Mytrofanova, I., Sypko, A. O., Sukhan, V. A. The influence of gender, age and profession-related differences on the verbal behavior of the subjects of association. Retrieved: 01.03.2015 from http: // fund-issled-intern.esrae.ru/5-63. Ufimtseva, N. V. (2006) Psikholingvistika i mezhkul’turnaya kommunikatsiya [Psycholinguistics and cross-cultural communication]. Rechevaya deyatel’nost’. Yazykovoe Soznanie. Obshchayushchiesya Lichnosti. Moscow; Kaluga: Eydos. Klimov, E.A. (2004). Psikhologiya professional’nogo samoopredeleniya [Professional self-determination in psychology], Moscow: Akademiya. Meshherjakov, B., Zinchenko, V. Vosprijatie [Perception]. In: Bol’shoj psihologicheskij slovar’ [Big Psychology Dictionary]. Retrieved: 01.03.2015 from http://www.gumer.info/bibliotek_Buks/Psihol/dict/03.php.